Antibiotic Use in Patients with Non-Specific Diarrhea at Tilongkabila Health Center, Bone Bolango Regency in 2023 - Halada, Yusri R.; Yahya, Isna Billah (West Science Interdisciplinary Studies, 2024)
Antibiotics that are not used wisely can trigger resistance problems. According to the World Health Organization (WHO), every year more than 1.27 million people worldwide die due to resistance to antimicrobials. The tolerance limit for prescribing antibiotics in patients with non-specific diarrhea according to WHO prescribing indicators is 8%. This study aims to determine the use of antibiotics in patients with non-specific diarrhea at the Tilongkabila Health Center. This research method uses a quantitative approach. Data was taken retrospectively with descriptive analysis. The results of the study showed that the use of antibiotics for patients with non-specific diarrhea was 10.6% with the dominant type of antibiotic used being amoxicillin at 63.2%. It was concluded that the use of antibiotics for patients with non-specific diarrhea at the Tilongkabila Health Center was not rational because it exceeded the prescription tolerance limits set by WHO.